IMPLEMENTASI PERMAINAN MISI PENJELAJAH DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KOMPUTASIONAL SEBAGAI WUJUD TRANSFORMASI ASWAJA - Syafaatul Maulida (Lembaga Pendidikan Ma'arif Nahdlatul Ulama, Kabupaten Malang, Indonesia, 2025)
This technological advancement requires students to develop computational thinking skills, which is a higher-order way of thinking. In Informatics at the junior high school/Islamic junior high school level, computational thinking is a compulsory subject from grades 7, 8, and 9. However, there are still challenges: many students struggle to understand computational scientific concepts, informatics learning is often perceived as rigid and limited to devices, and there has been no research specifically examining game-based learning with Aswaja values ​​in the context of computational thinking. Therefore, there is a need for engaging, unplugged learning methods, namely is Misi Penjelajah. This game is implemented to improve computational thinking skills while instilling Aswaja values ​​(tawasuth, tasamuh, tawasuts, and i’tidal) as a form of Aswaja Transformation. This study uses the Classroom Action Research (CAR) method with 28 students of class 8D MTs NU Pakis, Malang Regency as research subjects. The data used are observation data on computational thinking activities for students and assessment of the results of Misi Penjelajah, as well as a questionnaire on student learning motivation. The results of this study showed an increase in computational thinking skills, with 12 students (42.86%) in the very good category and 16 students (57.14%). In addition, students' learning motivation also increased, with 23 students (82.14%) having very high motivation to learn Informatics and 5 students (17.86%) having high motivation. This game is also able to foster the character of Aswaja values. This supports the formation of a moderate, tolerant, and balanced personality. Thus, this game is able to improve students' computational thinking, strengthen learning motivation, and shape students' characters who are strong in mind, body, feeling, and thinking.